Surface Patterning of PEDOT:PSS by Photolithography for Organic Electronic Devices. (2nd July 2015) - Ouyang, Shihong; Xie, Yingtao; Wang, Dongping; Zhu, Dalong; Xu, Xin; Tan, Te; Fong, Hon Hang
Abstract : Along with the development of organic electronics, conductive polymer of PEDOT:PSS has been attracting more and more attention because they possess various novel electrical, optical, and mechanical properties, which render them useful in modern organic optoelectronic devices. Due to its organic nature, it is lightweight and can be fabricated into flexible devices. For better device processing and integrating, it is essential to tune their surface morphologies, and photolithography is the best choice at present. In this paper, current PEDOT:PSS patterning approaches using photolithography are reviewed, and some of our works are also briefly introduced. Appropriate photolithographic patterning process for PEDOT:PSS will enable its application in future organic electronics.